ASSESSMENT OF CULTURAL HERITAGE ASSETS USING MARKET APPEAL-ROBUSTICITY MATRIX - Titis Wiji Ahyati; Riza Firmansyah; Devi Roza K. Kausar (Fakultas Pariwisata Universitas Pancasila, 2020)
Market Appeal Robusticity Matrix is ​​an effective assessment of cultural heritage assets to evaluate the potential market appeal and management of cultural heritage tourism (robusticity). It is important to determine appropriate policies and frameworks for better planning decisions in the future. This study aims to describe the preservation of cultural heritage at the Puppet Museum and analyze the valuation of cultural heritage assets at the Puppet Museum, Jakarta Old Town using Market Appeal-Robusticity Matrix. The research design used is qualitative analysis of Market Appeal-Robusticity Matrix. The results of this study have described the preservation of cultural heritage in the Museum, protection is done through maintenance and restoration, development is done by adding value to cultural heritage buildings by making it a Puppet Museum and the use of cultural heritage buildings is done by considering the interests of religion, social, culture and society . Preservation has been well implemented and adapted to the regulations of Law number 11 of 2010 concerning Cultural Heritage. Whereas the valuation of cultural heritage assets yields the value of the market attractiveness of the High Puppet Museum with a score of 51 and the resilience value of the building of the Medium Puppet Museum with a score of 40. In this assessment the Puppet Museum is in the